Competition and the Collective Management of Copyright - Hemphill, C. Scott (The Columbia Journal of Law & the Arts, 2011)
Discussions of the collective management of copyright tend to celebrate their subject. Much of the work collected in this volume focuses upon the significant economic value created by collective management organizations (“CMOs”), as well as the practical difficulties presented by any realistic effort to unlock that value. I have been assigned a different role to play. My task is to explain one downside of CMOs, namely the risk they pose to competition, and hence the limitations that antitrust law places upon their activities. These limits are familiar to many symposium participants. After all, two of the leading CMOs in the United States, ASCAP and BMI, have operated under an antitrust consent decree for the past sixty years. No article PDF is available.